2017
DOI: 10.1515/ijld-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Legal system: an additional variable in the analysis of short-term diachronic evolution of legal terminology

Abstract: The inclusion of specialised corpora in terminological studies since the early 1990s has allowed for the observation and description of the behaviour of terminology in authentic linguistic contexts. As a result, what is nowadays known as “Textual Terminology” (Bourigault & Slodzian 1999, Pour une terminologie textuelle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…By drawing the students' attention to the multilingual regime of the EU, it would be possible to make them aware of the complexity of multilingual primary and secondary term creation on the one hand (Peruzzo 2012;Temmerman 2018), and of the linguistic impact of EU legislation on national legislation on the other. Indeed, this article provides evidence in support of the fact that legal terminology does not necessarily evolve at the same pace as the underlying concepts, but it should also be borne in mind that every EU official language evolves separately (Peruzzo 2017). The terminologisation process in EU legal texts thus has multiple facets that future lawyers should be aware of.…”
Section: Short-period Diachronic Evolution From a Didactic Perspectivementioning
confidence: 75%
“…By drawing the students' attention to the multilingual regime of the EU, it would be possible to make them aware of the complexity of multilingual primary and secondary term creation on the one hand (Peruzzo 2012;Temmerman 2018), and of the linguistic impact of EU legislation on national legislation on the other. Indeed, this article provides evidence in support of the fact that legal terminology does not necessarily evolve at the same pace as the underlying concepts, but it should also be borne in mind that every EU official language evolves separately (Peruzzo 2017). The terminologisation process in EU legal texts thus has multiple facets that future lawyers should be aware of.…”
Section: Short-period Diachronic Evolution From a Didactic Perspectivementioning
confidence: 75%
“…The diachronic perspective visualized on Figure 5 below was supposed to examine whether legal grammar is subject to variation in time, with focus on the scrutinised verbal structures and -if 'yes' -which verbal structures are affected. The hypothesis related to variation in time rests on the positive empirical evidence on the time-related variation in legal terminology (See: Peruzzo, 2017), including the short-period perspective. The time span variable applied in this study is visualised as the three temporal categories according to which the texts making up the corpus were classified.…”
Section: Diachronic Perspectivementioning
confidence: 99%
“…Bhatia, 2014). Variations are further identified when relevant data are analysed against time-and culture-related axes (Peruzzo, 2017). The study indirectly draws on the assumptions found in corpus sociolinguistics (e.g.…”
Section: Introductionmentioning
confidence: 99%